TEACHING STRATEGY ON SPEAKING SKILLS TOWARD CELPAD IIUM STUDENTS - Siti Safura; Kholijah Asro (Leksema: Jurnal Bahasa dan Sastra, 2017)
Mastering a good strategy in teaching speaking constitutes one of the most important factors in teaching for educator. This is particularly so when student in other countries should speak English that basically is not his mother tongue. Good strategy in teaching speaking has been assumed as having a significant impact on students’ speaking skill. This study addressed the application and influence of a teaching strategy toward speaking skill for students. This study was conducted to17 students at Level 6 Section 12 and one teacher at CELPAD of IIUM. This study utilized mixed method between quantitative and qualitative by collecting data through observation, questionnaires and interview. The findings indicate that discussion strategy applied by the teacher was effective to improve students speaking skills. Students were more interested and motivated in speaking English using discussion.